Swot Analysis of Red Chili Agribusiness Development - Fadli Akbar Lubis; Budi Mulyara (JASc (Journal of Agribusiness Sciences), 2021)
This research was conducted in Sleman Regency, Yogyakarta Province. In their role, farmers only conduct farming at the level of production with relatively small added value or profit. Meanwhile, the processing and marketing subsystems tend not to be handled by them but by traders or other businessmen. This study aims to determine an alternative strategy for the development of red chili agribusiness in Sleman Regency. This research was conducted in December 2018 to January 2019 by conducting interviews with 11 respondents who were considered key informants. The method in this research is descriptive analytic based on primary and secondary data. The formulation of alternative strategies was analyzed by making Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, then continued with a grand strategy and SWOT analysis. Based on the research results, the competitive position of red chili agribusiness is in quadrant I (high market growth and strong competitive position).